2022
DOI: 10.1002/slct.202103437
|View full text |Cite
|
Sign up to set email alerts
|

An Enzymatic Glucose Biosensor Based on a Pencil Graphite Electrode Modified with Naphthalenedimide/3,4‐Ethylenedioxythiophene Conjugated Polymer and Enriched with Au Nanoparticles

Abstract: N,N′‐bis(2‐hexyl)‐2,6‐(3,4 ethylenedioxythiophene)‐1,4,5,8‐naphthalenimide (ENDI) monomer was electropolymerized on pencil graphite electrode (PGE) and used as a biosensor for glucose immobilization for the first time. After electropolymerization of ENDI monomer on PGE (AuNPs/PENDI/PGE), the intensity of the current signal was improved by using gold nanoparticles (AuNPs). The immobilization of the glucose oxidase (GOx) enzyme was carried out by using the cross‐linking reagent glutaraldehyde (GA) due to the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The platinum nanoparticulate on a poly(acryl acid)-modified SPCE electrode resulted in a good environment for the immobilization of GOx, with optimum values of 30 mg•mL −1 for enzyme loading and 1 h for the immobilization of GOx [107]. Other studies reporting the application of AuNPs [27,80], PtNPs [37], and AgNPs [73] confirmed these advantageous properties as well. A microelectrode glucose biosensor based on a three-dimensional hybrid nanoporous platinum/GO nanostructure was developed [39].…”
Section: Nanomaterialsmentioning
confidence: 63%
See 1 more Smart Citation
“…The platinum nanoparticulate on a poly(acryl acid)-modified SPCE electrode resulted in a good environment for the immobilization of GOx, with optimum values of 30 mg•mL −1 for enzyme loading and 1 h for the immobilization of GOx [107]. Other studies reporting the application of AuNPs [27,80], PtNPs [37], and AgNPs [73] confirmed these advantageous properties as well. A microelectrode glucose biosensor based on a three-dimensional hybrid nanoporous platinum/GO nanostructure was developed [39].…”
Section: Nanomaterialsmentioning
confidence: 63%
“…Most amperometric glucose biosensors are based on glucose oxidase (GOx, EC 1.1.3.4), which employs oxygen as its electron acceptor to selectively catalyse the oxidation of β-D-glucose to β-D-glucono-1,5-lactone and hydrogen peroxide [ 24 ]. For these applications, GOx is mainly obtained from fungal sources such as Aspergillus niger ( An GOx) [ 21 , 25 , 26 , 27 , 28 ] and Penicillium vitale [ 29 , 30 ]. An GOx is especially well known and preferred because of its stability over a wide range of temperature and pH together with its excellent selectivity for glucose.…”
Section: Enzyme-based Biosensors For Food Analysismentioning
confidence: 99%
“…After electropolymerization of ENDI monomer on PGE (AuNPs/PENDI/PGE), the intensity of the current signal was improved by using gold nanoparticles (AuNPs). 18 Metallic nanoparticles (NPs) are the preferred form for biosensors in order to improve the conductivity of the electrode due to their large surface area. For this reason, NPs are used in biosensor applications to further increase the conductivity of conductive polymers.…”
mentioning
confidence: 99%